Fabrication of samaria doped ceria thin film on porous substrate by slurry spin coating - Lee, Tsung-han (2016)
Samaria doped cena (SDC) with fluorite structure has higher ionic conductivity than Yttria stabilized zirconia (YSZ) for low temperature solid oxide fùel cells (LT-SOFCs). SDC powder with cubic fluorite structure was synthesized by co-precipitation method at calcined temperature of 600 °C. The average crystallite size of the calcined SDC powder is around 15 nm determined from XRD data. The thickness of SDC thin film deposited on porous silver substrate is nearly proportional to the coating layers tìich are controllable by repeating the spin coating process. The spin-coated SDC thin film on porous silver substrate showed partially dense and uneven microstructure after sintered at 800 oc fbr 10 hours. Moreover, the microstructures were changed to notably porous structure at sintering temperature of 900 and 1000 °C for 10 hours. The SDC thin film spin-coated on Si substrate showed identical surface morphologies and more even microstructures with on porous silver substrates at the corresponding sintering temperature. The fully dense SDC thin film was obtained on the Si substrate at sintening temperature of 1300 oc for 10 hours. The result indicates that the sintering temperature is not enough for fully sintering the SDC powder into dense film and the porous substrate would make the uneven microstructure.